2019
DOI: 10.1016/j.heares.2019.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selective auditory-nerve damage on the behavioral audiogram and temporal integration in the budgerigar

Abstract: Auditory-nerve fibers are lost steadily with age and as a possible consequence of noise-induced glutamate excitotoxicity. Auditory-nerve loss in the absence of other cochlear pathologies is thought to be undetectable with a pure-tone audiogram while degrading real-world speech perception (hidden hearing loss). Perceptual deficits remain unclear, however, due in part to the limited behavioral capacity of existing rodent models to discriminate complex sounds. The budgerigar is an avian vocal learner with human-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 93 publications
1
13
0
Order By: Relevance
“…Theoretical reasoning by Lopez-Poveda and Barrios (2013) and perceptual model simulations by Marmel et al (2015) suggest that synaptopathy involves a substantial loss of low-threshold AN fibers in addition to the larger loss of high-threshold fibers, which is predicted to elevate the detection threshold for brief tones, without significantly elevating the thresholds for longer sounds. The results of Wong et al (2019) in the budgerigar undermine this approach and the experimental data currently available are not adequate to allow a recommended protocol for this test.…”
Section: Suggestions For Methodological Approaches To Investigate Synmentioning
confidence: 99%
“…Theoretical reasoning by Lopez-Poveda and Barrios (2013) and perceptual model simulations by Marmel et al (2015) suggest that synaptopathy involves a substantial loss of low-threshold AN fibers in addition to the larger loss of high-threshold fibers, which is predicted to elevate the detection threshold for brief tones, without significantly elevating the thresholds for longer sounds. The results of Wong et al (2019) in the budgerigar undermine this approach and the experimental data currently available are not adequate to allow a recommended protocol for this test.…”
Section: Suggestions For Methodological Approaches To Investigate Synmentioning
confidence: 99%
“…Similarly, most mice with .95% AN loss because of ouabain exposure show normal tone sensitivity in quiet (Chambers et al, 2016). Finally, a recent study in budgerigars found no impact of 40-70% AN damage from kainic acid (KA), even for tone durations as short as 20 ms (Wong et al, 2019). Other studies based on acoustic-startle responses have found diverse changes in behavioral reflex strength that vary with the magnitude of AN loss and specific test paradigm (Hickox and Liberman, 2014;Chambers et al, 2016;Lobarinas et al, 2017), but translation of startle results to auditory perception remains controversial Klump, 2015, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This speaks to the importance of using measures in addition to threshold when attempting to elucidate the effects of noise on auditory processing. Considering slope may become increasingly important in understanding the effects of hearing impairment, as recent hidden hearing loss studies have demonstrated a lack of effect on threshold measures of temporal integration (Marmel et al, 2020;Wong et al, 2019), but did not asses psychometric slope.…”
Section: Psychometric Function Slopementioning
confidence: 99%